Essential Systemic Arterial Hypertension in Northeastern Brazil: An ecological analysis of hospitalizations using Poisson regression (2020–2024) (Research, Society and Development, 2025)
Systemic arterial hypertension (SAH) is a highly prevalent chronic condition with a substantial impact on cardiovascular and renal morbidity and mortality. In settings of population aging and social inequalities, failures in diagnosis, treatment, and control increase preventable decompensations and hospitalizations, placing pressure on health systems. This study aimed to analyze the profile and temporal trend of hospitalizations for essential arterial hypertension (ICD-10 I10) in Northeastern Brazil from 2020 to 2024, in order to support prevention strategies and chronic care organization within the Brazilian Unified Health System (SUS). Hospitalizations were described by state, sex, age group (≥20 years), and race/color (including “no information”), and annual variation was estimated using Poisson regression (IRR and 95% CI), identifying increasing, decreasing, or stable trends. A retrospective ecological time-series study was conducted using SIH/SUS data. Records were aggregated by federative unit and demographic strata, and overdispersion was assessed with sensitivity analyses when necessary. Northeastern Brazil recorded 70,816 hospitalizations in the five-year period, mostly in Maranhão and Bahia. Among adults, females predominated, with higher representation among those aged 60–79 years and relevant contribution from individuals ≥80. Mixed-race (pardo) individuals constituted most records, and missing race/color data persisted. State-specific trends formed a heterogeneous mosaic shaped by demographic and organizational characteristics. The hospital burden of hypertension remains high and unequal in the region. Strengthening primary care, ensuring continuous access to antihypertensives, improving transitional care, and qualifying race/color recording are recommended to reduce preventable hospitalizations.